Skandimentalitet: Moral og amoral i skandinavisk privilegiesensibilitet og i "The Square" - Sharma, Devika (K&K - Kultur og Klasse, 2021)
Looking to Swedish director Ruben Östlund’s 2017 movie The Square, this article describes the ways in which Scandinavian privilege sensibility makes itself known as a tense reflection on, or struggle over, the value of moral sentiments such as sympathy, compassion, solicitude, and pity. In contemporary Scandinavian culture, it has become an affective habit, I suggest, to be suspicious of the moral sentiments, which will therefore typically be regarded and experienced as morally embarrassing states of feeling. Thus, the moral sentiments are always in risk of becoming signs of something immoral in the feeling subject, whether an individual or a collective subject. Privilege sensibility indicates to us something important about the ways in which we respond to inequality and to our own position in unequal social fields of relation, and central to this sensibility is, I argue, a structure of feeling according to which noble emotions may turn ugly, while conventionally ugly feelings may, conversely, turn beneficial and legitimate. ”Scandimentality” will be my name for this structure of feeling and its aesthetic forms.